Rifaximin plus cefotaxime versus cefotaxime alone in treatment of spontaneous bacterial peritonitis in patients with cirrhosis - Asmaa N Mohammad; Mahmoud K Elsamman; Amr M Zaghloul; Hameda H Mohamed; Walaa I Mohammed (SpringerOpen, 2018)
Background/purpose of the study Spontaneous bacterial peritonitis (SBP) is a cause of significantly higher morbidity and mortality in patients with cirrhosis. This study was conducted to assess the effect of adding rifaximin to cefotaxime in treatment of SBP. Materials and methods The study was a prospective one that involved 98 patients with cirrhosis with SBP, who were divided randomly into two equal groups. Patients in group I received cefotaxime, whereas patients in group II received a combination of cefotaxime and rifaximin. Patients were evaluated clinically, and diagnostic aspiration was repeated on the third day of antibiotic therapy. Results Both groups showed significant reduction in white blood cells on the third day compared with the first day (P<0.0001). Polymorphonuclear leukocyte count in ascetic fluid in both groups showed significant reduction on the third day compared with the first day, and the reduction was statistically significant in group II compared with group I (P<0.0001). One the third day of therapy, serum creatinine levels in group I and group II were 1.61±0.19 and 1.28±0.37, respectively. Both groups showed significant decrease in serum creatinine level. The reduction in group II compared with group I was statistically significant, with P value less than 0.0001. Conclusion Rifaximin plus cefotaxime showed some favorable effects in treatment of SBP than cefotaxime alone. However, the clinical effects of these effects need to be clarified in further studies.